ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA KELAS X PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK - Novi Nurrizbaeni; Wahyu Setiawan (Departement of Mathematics Education, 2019)
The purpose of this study is to find out and analyze how students' problem solving abilities in working on mathematical problems, especially in the matter of absolute value equality. The subjects in this study were students of class XA MA Al-Barry in West Bandung. The Instsrumen used consists of written tests in the form of essay questions, namely from the four problem solving indicators into 5 questions. This research method uses descriptive qualitative analysis with case studies, so that researchers can see the mistakes students can make while working on the problem. Processing data is calculated in the form of percent to find out the extent of the achievement of indicators of problem solving ability. Data achievement indicators understand the problem of 98.75%, plan completion of 70.5%, resolve problems 82.2%, and check answers 53.07% .